The Manifestation of Europeanness in the Soviet Lithuanian poetry: the Aesthetic Liberation of Identity - Bagdonė, Karolina (Colloquia, 2018)
This paper analyses three – the national, European and Soviet – identity models, their collision, overlap, and transformation. It focuses on the phenomenon of the Lithuanian national identity, which at the same time is locally distinct, but also open to Europe (Europeanness). The paper also presents an analysis of how Soviet ideology acted on and formed people’s self-depiction and how it emerged in Lithuanian poetry in the second part of the 20th century. For my sociological comparative analysis I wanted to represent a few distinct examples of identities and chose the creative works of two famous Lithuanian poets – Eduardas Miezelaitis and Sigitas Geda. Miezelaitis could be considered as one of the founders of Soviet modernist poetry who gave the impression of a free poetic language within the context of the Soviet regime. Nevertheless, he expressed an identity which is characterized by defensiveness, overprotectiveness, and a nomenclatural position. The poetry of Geda is an example of an expression of an European identity. It is characterized by an innovative relation to tradition, a search for a different and anti-ideological reader, and a complex poetic language.
Keywords: identity; nationalism; Lithuanian; European; Soviet; poetry